Sightings of southern right whales (Eubalaena australis) in Namibian waters, 1971-1999 - Roux, J-P.; Best, P.B.; Stander†, P.E. (J. Cetacean Res. Manage., 2020)
Southern right whales were originally abundant in Namibian waters in winter and spring. They were either eradicated from the region or driven to extremely low numbers more than a century ago. Since 1971, 36 incidental sightings and three aerial surveys confirm the regular presence of the species within its historical calving range, between June and December. Calving has been recorded in four successive years and at least 10 calves were born in the area between 1996 and 1999, confirming the existence of a small established breeding population. This represents a northward extension of the hitherto known modern regular calving range in the South East Atlantic Ocean by more than 1,000km.